Iqbāl aur Magẖrib - Al-i-Ahmad Suroor, 1912- (Iqbāl Insṭīṭiyūṭ, Kashmīr Yūnivarsiṭī ; taqsīmkār, Maktabah-yi Jāmiʻah, 1981)
Collection of articles on the influence of West on the poetry of Sir Muhammad Iqbal, 1877-1938.